Creative Destruction and the HIDCL - Butler, Christopher (Hydro Nepal: Journal of Water, Energy and Environment, 2014)
Not Available. DOI: http://dx.doi.org/10.3126/hn.v14i0.11248 HYDRO Nepal Journal Journal of Water Energy and Environment Volume: 14, 2014, January Page: 21-22